BAHASA AKADEMIK DAN NON AKADEMIK SANTRI DI PONDOK PESANTREN BAHRUL ULUM TANGGAMUS (Studi Analisis Persepktif Teori Interaksionisme Simbolik) - Khabibul Khoiri (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2023)
Humans are social beings who cannot be separated from the process of interacting with others to meet their needs in society. Likewise, what is done by the students who carry out the interaction process at the Bahrul Ulum Islamic Boarding School also has a uniqueness, namely in the form of academic and non-academic language in accordance with the culture or binding rules at the Islamic boarding school. However, the language used in the Islamic boarding school is not interpreted as understood by the majority of the community. Therefore, researchers through the field research method succeeded in uncovering and digging up information related to the languages ​​used in the bahrul ulum Islamic boarding school so that it can provide information and experience to the non-Islamic boarding school community so that they can find out the languages ​​used by the students in the Islamic boarding school.